Review of methods for collecting data on passenger flow dynamics (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article is dedicated to the analysis and review of methods for collecting data on passenger flow dynamics in urban environments. Considering the growing volume of urban passenger transportation and the need for efficient management of transport flows, data collection and analysis become critically important elements of urban planning and management. The paper presents a systematization of existing methods, evaluates their advantages and disadvantages, and provides recommendations for their application under various conditions. The research is based on a review of scientific literature, analysis of technical documentation, interviews with experts, and practical case studies from different countries. The results of the study may be useful for urban management bodies, transport companies, research institutions, and everyone involved in urban transport and mobility issues.
Keywords: Passenger flow, data collection methods, urban transport, transport flows, data analysis, geographic information systems, transport infrastructure optimization